LEVERAGING COUNSELING IN COMBATING HEALTH RISKY BEHAVIORS IN NIGERIA’S TERTIARY EDUCATION: A CASE STUDY OF EBONYI STATE (IJOVTECH, 2026)
The problem of health risky behaviors in students of the tertiary institutions in Nigeria is the major problem of societal health as it leads to higher morbidity and mortality rates. This paper examines how counseling interventions can be used to reduce such behaviors using Ebonyi State as the case study. A mixed-methods design was used to gather primary data in the form of surveys and 500 undegraduates at Ebonyi State University and Alex Ekwueme Federal University Ndufu-Alike. The theoretical framework that was used in the research design is the Health Belief Model to study the perception of all these (susceptibility, severity, benefits and barriers to behavior change). The prevalence rate of risky behaviors was found to be high as alcohol use (45.2%), smoking (28.4%), drug abuse (32.6%), and unsafe sexual behavior (41.8%). The demographics were used to indicate that male students of lower socioeconomic status with ages between 18-24 years were more likely to engage in such behaviors. Interventions like cognitive behavioral therapy sessions and peer-led programs proved an effective way of reducing the reported risky activity by 25% after the interventions. The research paper demonstrates how counseling services should integrate with the health services of universities to facilitate a healthier lifestyle. Obstacles have been found to be stigma, lack of access to counselors and even cultural norms. Suggestions include policy improvements to ensure the mandatory tertiary institution counseling units and health-educator training. This study adds to the literature on health education in developing settings, highlighting the effectiveness of the specific form of counseling in promoting the change in behavior among the vulnerable youth groups.